Circulating anti-phospholipase A2 receptor antibodies as a diagnostic and prognostic marker in Greek patients with idiopathic membranous nephropathy - a retrospective cohort study - Provatopoulou Simella; Kalavrizioti Dimitra; Stangou Maria; Kouri Maria-Nikoleta; Kalliakmani Pantellitsa; Papasotiriou Marios; Papachristou Evangelos; Goumenos Dimitrios S.; Papagianni Aikaterini (Sciendo, 2019)
Introduction. Circulating autoantibodies against phospholipase A2 receptor (anti-PLA2R) are recognized as key elements in the pathogenesis of idiopathic membranous nephropathy. In current clinical practice, they are increasingly gaining attention as novel tools for diagnosis and disease monitoring. We investigated the diagnostic and prognostic utility of anti-PLA2R antibody measurements in Greek patients with biopsy-proven membranous nephropathy.